2015
DOI: 10.5812/jjhs.7(2)2015.27996
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude of Radiology Technologists Towards Cardiopulmonary Resuscitation

Abstract: Background:The number of casualties and critically ill patients referred to radiology departments increased during the past decade, which caused the risk of cardiac arrest in radiology departments to increase considerably. Objectives: The current study aimed to evaluate the knowledge and attitude of radiology technologists regarding Cardiopulmonary Resuscitation (CPR). Patients and Methods: After approval a cross sectional study was designed. Ninety five radiology technologists (male and female) were selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…13 The AHA recommends that the interval between initial CPR training and a refresher course should not be more than 2 years; however, studies evaluating the deterioration of CPR skills amongst medical personnel have shown a decline at 2-12 months following completion of training. 14,15,16,17,18,19 With regard to contrast media reactions and management, most of the radiologists, residents and radiographers performed relatively well in the identification of mild and severe anaphylactic reactions and in their knowledge of the risk factors for an adverse reaction. At least 82% of health workers correctly identified a symptom of mild reaction, a symptom of severe reaction and a risk factor for anaphylactic reaction.…”
Section: Discussionmentioning
confidence: 99%
“…13 The AHA recommends that the interval between initial CPR training and a refresher course should not be more than 2 years; however, studies evaluating the deterioration of CPR skills amongst medical personnel have shown a decline at 2-12 months following completion of training. 14,15,16,17,18,19 With regard to contrast media reactions and management, most of the radiologists, residents and radiographers performed relatively well in the identification of mild and severe anaphylactic reactions and in their knowledge of the risk factors for an adverse reaction. At least 82% of health workers correctly identified a symptom of mild reaction, a symptom of severe reaction and a risk factor for anaphylactic reaction.…”
Section: Discussionmentioning
confidence: 99%